Brief review of logit models applications in regional studies - Markowska, Małgorzata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The problems referring to the functioning of economy are closely related to a territory. The place of their occurrence, whether it is a country, a region or a smaller territorial unit, implies the scale and the benchmark for carrying out analyses. Numerous phenomena within the area of economic research are of complex nature and, moreover, it is frequently difficult to express them in a measurable form. The solution to such “inconvenience” is e.g. the application of qualitative variables. Logistic regression is one of the tools allowing the assessment of dependence and prediction in case of qualitative variables of dichotomous type. The purpose of the study is to review the applications of logit models in regional studies
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 476, s. 9-17
Keywords: review; logit models; regional studies; przegląd; modele logitowe; badania regionalne